Pengembangan Produk Branding Sebagai Penguatan Dalam Pemasaran Rumah Produksi Jamur Pada Paimo Farm - Dewi Puspa Arum; Siti Nurhaliza; Betaria Novila Ananda Putri; Fatima Azrina Pramesthi; Dini Hiqmatul Hayati; Muhammad Handito Perwira Negara; Muhammad Faiz Harby (Institut Nalanda, 2023)
MSMEs play an important role in economic growth which has a direct impact on regional economic development. In the Ngadirejo Village, Kepanjenkidul District, Blitar City, there is an UMKM